"Depopulation, community-based tourism, and community resilience in southwest Spain". (December 2021) - Cáceres-Feria, Rafael; Hernández-Ramírez, Macarena; Ruiz-Ballesteros, Esteban
Abstract: Concern about depopulation and its effects has fuelled the search for economic alternatives to traditional agricultural activities in rural areas. One of the most frequently used strategies is the promotion of community-based tourism (CBT), an activity that, when organised and managed locally, can effectively counter the crisis. CBT can promote resilience by mobilising community members and their resources. This article uses an ethnographic case study conducted in SW Spain to further our understanding of two strategic phenomena for the study of CBT and its potential effects in the fight against rural depopulation: a) the contribution of CBT to community building, and b) the role of CBT in developing community resilience. The results have shown that, beyond an economic strategy, CBT can be a valuable instrument of collective action, promoting social relations and enhancing community well-being. Ultimately, building community in the face of rural crisis. Highlights: Rural communities severely affected by depopulation and with a community life weakened, finds a means of social reactivation in CBT. CBT can be a valuable instrument of collective action, promoting social relations and enhancing community well-being. The key factors for understanding the success of CBT are found in the community itself, in its social capital. CBT contributes significantly to community resilience by mobilising members of the community and their resources.